2021
DOI: 10.1117/1.nph.8.2.025002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a new generation of wearable high-density diffuse optical tomography technology via retinotopic mapping of the adult visual cortex

Abstract: Significance: High-density diffuse optical tomography (HD-DOT) has been shown to approach the resolution and localization accuracy of blood oxygen level dependent-functional magnetic resonance imaging in the adult brain by exploiting densely spaced, overlapping samples of the probed tissue volume, but the technique has to date required large and cumbersome optical fiber arrays. Aim : To evaluate a wearable HD-DOT system that provides a comparable sampling density to large, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 61 publications
(69 reference statements)
0
42
0
Order By: Relevance
“…Looking towards the future of EEG–fNIRS systems, investigations into ergonomic designs (i.e., wearable, miniaturized, lightweight, flexible) will continue to remain of key interest for long-term monitoring, wearability, and subject comfort. Improvements in resolution, high-speed ADCs, sensitive amplifiers, and precise logic control will be necessary to obtain the large dynamic range needed for high channel count fNIRS systems [ 8 , 62 , 63 , 64 ]. Consequently, more advanced data interfaces and control schemes would be required to ensure a large channel count, large dynamic range, and high-speed data acquisition and transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking towards the future of EEG–fNIRS systems, investigations into ergonomic designs (i.e., wearable, miniaturized, lightweight, flexible) will continue to remain of key interest for long-term monitoring, wearability, and subject comfort. Improvements in resolution, high-speed ADCs, sensitive amplifiers, and precise logic control will be necessary to obtain the large dynamic range needed for high channel count fNIRS systems [ 8 , 62 , 63 , 64 ]. Consequently, more advanced data interfaces and control schemes would be required to ensure a large channel count, large dynamic range, and high-speed data acquisition and transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success, the conformability (to the curved human scalp) and subject comfort of these electrodes still can be improved. Besides this, how to fit these relatively bulky electrodes into a miniaturized, compact wearable fNIRS module/functional blocks [ 8 , 61 , 62 , 63 ] remains unclear.…”
Section: Eeg Electrodes and Front-end Amplifiersmentioning
confidence: 99%
“…The availability of CW-HD-DOT systems is increasing rapidly for both adult and pediatric studies owing to the demonstrated improvements in image quality obtained with HD arrays. 1 , 12 , 13 , 55 62 Most research groups still utilize CW systems for wide-field optical imaging of human brain function as these systems are significantly less expensive than FD and TD systems. However, recent studies have highlighted a renewed focused on HD arrangements of FD measurements due to the value in incorporating the additional phase measurements to realize the potential for improved image quality and potential access to absolute oxygenation concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI is the most widely used method to diagnose pituitary tumors, this technique is quite costly and time-consuming, especially since the pituitary gland requires specialized imaging sequences. In addition, MRI has contraindications for electronic or metal implants (such as pacemakers, cochlear implants, aneurysm clips, and surgical devices) ( 7 ) and claustrophobia.…”
Section: Introductionmentioning
confidence: 99%